Mimicking human movement with robots: control of an anthropomorphic robotic arm using a glove-based system as an educational tool - Oliveira, Ricardo (2019)
The present paper proposes, as an educational activity, the design of a system that allows the control of a robotic manipulator by using a sensory glove and an arm sleeve. The robotic manipulator features a robotic arm and hand, with a total of 10 degrees of freedom, using ten servo motors as actuators. On the other hand, the controller component features six flex sensors and two Inertial Measurement Units (IMUs). Due to the low force exerted by the motors, along with an issue regarding the reference frame of one of the IMUs, the robotic hand and wrist were detached from the robotic arm and both were tested separately. The results from real-time testing showed that the system successfully replicated the movements performed by the user. However, the system requires further improvements, mainly due to its lack of precision and limited degrees of freedom, along with other hardware issues. Regardless, an optimized design of the proposed system can have various applications, such as the manipulation of objects in hazardous conditions.